Co-cultivation With 5-Azacytidine Induced New Metabolites From the Zoanthid-Derived Fungus Cochliobolus lunatus - Wu, Jing-Shuai; Shi, Xiao-Hui; Zhang, Ya-Hui; Yu, Jia-Yin; Fu, Xiu-Mei; Li, Xin; Chen, Kai-Xian; Guo, Yue-Wei; Shao, Chang-Lun; Wang, Chang-Yun (Frontiers in Chemistry, 2019)
The zoanthid-derived fungus Cochliobolus lunatus (TA26-46) has been proven to be a source of bioactive 14-membered resorcylic acid lactones (RALs). In the present study, chemical epigenetic manipulation was applied to this fungal strain with a DNA methyltransferase inhibitor resulting in the significant changes of the secondary metabolites. Cultivation of C. lunatus (TA26-46) with 10 μM 5-azacytidine in Czapek-Dox liquid medium led to the isolation of new types of metabolites, including two α-pyrones, cochliobopyrones A (1) and B (2), along with three isocoumarins (3–5) and one chromone (6). The planar structures of the new compounds (1‒2) were elucidated by comprehensive analyses of NMR and HRESIMS data. Their challenging relative configurations were established by a combination of acetonide reaction, coupling constants and NOESY correlations analysis, and DP4+ probability calculation. Their absolute configurations were determined by comparing with the ECD calculation data of the fragment molecules, 6-(1,2-dihydroxypropyl)-4-methoxy-2H-pyran-2-ones. It is the first time to obtain α-pyrone compounds with the epoxy ring or bromine atom on the seven-numbered side chain. It could be concluded that chemical epigenetic agents could induce C. lunatus to produce new types of secondary metabolites differing from its original products (RALs).